Modification of Snack Bar Cheubit with Addition of Seaweed (Eucheuma Cottonii) and Beet (Beta Vulgaris L.) as a Snack Alternative for Elementary School Children Obesity - Faradillah Farida; Agus Heri Santoso; Nur Rahman (Journal of Local Therapy, 2022)
Obesity has become a nutritional problem in Indonesia. The prevalence of obesity in children aged 5 until 12 years in Indonesia is quite high, namely 8.0 percent, while the prevalence of obesity in East Java is above the national rate or greater than 8.0 percent. Efforts to prevent and cope with obesity in children need to be done, one of them by making the snack alternative like snack bar with the addition of seaweed and beet. Seaweed and beet is a good ingredient for obesity because it has high fiber content and low fat. The aim of this research is to know the effect of Modification of Snack Bar Cheubit with Addition of Seaweed or Eucheuma cottonii and Beet or Beta vulgaris L. as a Snack Alternative for Elementary School Children Obesity to fiber content, chemical quality, energy value, and organoleptic quality. The research type was laboratory experiment with Randomized Complete Random Design or RAL design using 3 treatment levels, is the proportion of wheat flour is seaweed by beet is P1 10 by 54 by 15, P2 10 by 49 by 20, and P3 10 by 44 by 25. Each formulation is done 3 times replication so that there are 9 units of research. The results of the statistical test using Oneway Anova showed that the proportion of seaweed and beet gave no significant difference to fiber content, protein content, fat content, moisture content, ash content, carbohydrate content, and energy value of snack bar. Assessment of organoleptic qualities using the Kruskal Wallis statistical test with advanced Mann Whitney test gave a significant difference to color, taste, and texture, however, a not significant difference to the aroma of the snack bar. The best treatment level is P3 treatment level in 100 gram which contains energy value 209,86 kcal, protein 3,08 gram, fat 2,99 gram, carbohydrate 42,67 gram and fiber 2,12 gram.